Teachers’ Attitudes Towards Desirable Intercultural Competences Necessary for Working in Multicultural Classrooms - Adili, Bujar; Ameti, Makfirete; Zenki-Dalipi, Arbresha (Journal of Educational Technology and Instruction, 2023)
Teachers’ intercultural competence is a key factor in the consistent implementation of intercultural principles in teaching practice. The study conducted among primary school teachers in North Macedonia aimed to examine the effect of sociocultural factors on the perception of desirable intercultural competencies for working in multicultural classrooms. 217 primary school teachers from multiethnic regions in North Macedonia participated in the study. The Scale for Assessing Desirable Intercultural Competences (SADIC) was used to collect data. Descriptive statistical procedures were employed in data processing to determine descriptive characteristics, and the comparison of respondents’ attitudes was conducted using the t-test and ANOVA. Additionally, a post hoc test (Scheffe’s test) was performed to determine the significance of the differences. The results showed a significant effect of sociocultural factors on the perception of desirable intercultural competencies. These perceptions range from teamwork skills to motivation for continuous learning and education, non-violent conflict resolution skills, a critical approach to societal events, openness to different cultures, and the ability to see problems from the perspective of culturally different students. This research forms a potential basis for considering the approach to designing a school that is open to diversity.